Follicular development status and profile of 17Î² estradiol and cortisol levels during spawning cycle in Oreochromis mossambicus (Peters) - Ganesh, C. B. (Indian Journal of Fisheries, 2014)
In this study, the duration of different phases of the ovarian cycle, the pattern of follicular development and profile of serum levels of 17Î² estradiol (E2) and cortisol were determined in female tilapia, Oreochromis mossambicus. Five oocyte developmental stages, namely chromatin-nucleolous, perinucleolar, cortical alveolar, vitellogenic and early maturation stages were identified. The mean number of stage I (previtellogenic) follicles showed continuous proliferation irrespective of phases of the ovarian cycle, while the stage II (previtellogenic) follicles increased significantly (p